Semantic Grid resource discovery based on SKOS ontology. (2017) - Chergui, Nabila; Chikhi, Salim; Kechadi, Tahar
In large-scale distributed environments like dynamic Grids, an efficient and scalable resource discovery mechanism is required. Hybrid techniques based on node clustering are considered among solutions that guarantee the efficiency and the scalability at the same time. However, lack of a good representation of nodes in these environments often results in an irrelevant grouping of nodes. Combining hybrid techniques with Semantic Web technologies would bring more benefits to resource discovery. This paper introduces a semantic clustering of nodes based on their domains of interest to form groups called federations. It presents a new process for constructing federations and a three-layered overlay network. The proposed process is based on a SKOS lightweight ontology that describes domains of applications in the Grid. We conduct extensive simulations to evaluate the performance of the proposed approach; the experimental results demonstrate its efficiency and its ability to scale up with the system size.